2009
DOI: 10.1038/sj.bjc.6605365
|View full text |Cite
|
Sign up to set email alerts
|

Activation and clinical significance of the unfolded protein response in breast cancer

Abstract: Introduction: The tumour microenvironment is hypoglycaemic, hypoxic and acidotic. This activates a stress signalling pathway: the unfolded protein response (UPR). The UPR is cytoprotective if the stressor is mild, but may initiate apoptosis if severe. Activation of the UPR in breast carcinoma is induced by microenvironmental stress such as glucose and oxygen deprivation, but may also be linked to oestrogen stimulation. It may be clinically significant as it may alter chemosensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 24 publications
3
118
0
Order By: Relevance
“…Our group originally demonstrated that cell-surface GRP78 enables tumor targeting by circulating ligands in vivo (18,19), an observation confirmed by independent investigators (20,21). Both hormone receptor-positive and -negative breast cancers appear to overexpress GRP78 (22,23), and high levels of GRP78 in patients correlate to poor responses to chemotherapy and lower survival rates (24). However, despite its promise as a functional molecular target and as a potential prognostic marker in human breast cancer, the role of GRP78 in patients with IBC remains unclear, hence the impetus for this work.…”
mentioning
confidence: 75%
“…Our group originally demonstrated that cell-surface GRP78 enables tumor targeting by circulating ligands in vivo (18,19), an observation confirmed by independent investigators (20,21). Both hormone receptor-positive and -negative breast cancers appear to overexpress GRP78 (22,23), and high levels of GRP78 in patients correlate to poor responses to chemotherapy and lower survival rates (24). However, despite its promise as a functional molecular target and as a potential prognostic marker in human breast cancer, the role of GRP78 in patients with IBC remains unclear, hence the impetus for this work.…”
mentioning
confidence: 75%
“…The UPR and its associated factors have been implicated in resistance to numerous cancer therapies (Pyrko et al 2007, Scriven et al 2009, Al-Rawashdeh et al 2010, Chen et al 2011. For example, increased expression of ATF4 is associated with decreased sensitivity to several therapies (Tanabe et al 2003, Igarashi et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…These ER stress stimuli lead to the activation of the UPR pathway that can provide either pro-survival signals to reestablish cellular homeostasis or cell death signals if the stress is prolonged and unresolved (Scriven et al 2009;Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%